Audit of Hospital Management Information Systems Based on The COBIT 4.0 Framework - Gabriel Firsta Adnyana; Rai Riska Resti Wasita; Andreas Adi Trinoto (Faktor Exacta, 2025)
Wangaya Regional General Hospital aspires to be the preferred healthcare facility by delivering innovative, high-quality health services. Strategically located, it serves as a key health service provider in the area. This research seeks to assess the application of information technology in healthcare through the COBIT 4.0 framework, encompassing four domains: (PO) Plan And Organize, (AI) Acquire And Implement, (DS) Deliver And Support, and (ME) Monitor And Evaluate. The objective is to enhance medical services at Wangaya Regional General Hospital (RSUD) in Denpasar, ensuring that its operations are effective and efficient, thereby fulfilling the Hospital's mission as a Regional Public Service Agency. The study utilizes primary data, including patient visit statistics and handling procedures, alongside interviews with medical staff. This data undergoes an audit via the COBIT 4.0 Framework to ascertain Maturity Levels (ML). The findings of this study will serve as a valuable reference for future developmental strategies for Wangaya Regional Hospital in Denpasar City